2013
DOI: 10.1016/j.neuroimage.2013.05.108
|View full text |Cite
|
Sign up to set email alerts
|

Resting state network estimation in individual subjects

Abstract: Resting-state functional magnetic resonance imaging (fMRI) has been used to study brain networks associated with both normal and pathological cognitive function. The objective of this work is to reliably compute resting state network (RSN) topography in single participants. We trained a supervised classifier (multi-layer perceptron; MLP) to associate blood oxygen level dependent (BOLD) correlation maps corresponding to pre-defined seeds with specific RSN identities. Hard classification of maps obtained from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
281
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 240 publications
(296 citation statements)
references
References 90 publications
11
281
0
4
Order By: Relevance
“…1) involved the temporo-parietal junction (caudal superior temporal gyrus, supramarginal and angular gyri) and the posterior portion of the inferior frontal gyrus. These results are similar to those described as in previously task-related fMRI studies (Corbetta and Shulman 2002;Shulman et al 2010) and rs-fMRI connectivity studies (Fox et al 2006;Shulman et al 2009;Hacker et al 2013) Repeated measures ANOVA revealed a significant interaction between the group and the CPRS scores (F (3,308) =206.25; p < 0.001). Post-hoc independent-sample t-test are summarized in table 3 and revealed significant differences between the CPRS scores for the three groups (see Fig.…”
supporting
confidence: 90%
“…1) involved the temporo-parietal junction (caudal superior temporal gyrus, supramarginal and angular gyri) and the posterior portion of the inferior frontal gyrus. These results are similar to those described as in previously task-related fMRI studies (Corbetta and Shulman 2002;Shulman et al 2010) and rs-fMRI connectivity studies (Fox et al 2006;Shulman et al 2009;Hacker et al 2013) Repeated measures ANOVA revealed a significant interaction between the group and the CPRS scores (F (3,308) =206.25; p < 0.001). Post-hoc independent-sample t-test are summarized in table 3 and revealed significant differences between the CPRS scores for the three groups (see Fig.…”
supporting
confidence: 90%
“…BA44 is located immediately anterior to the ventralmost aspects of the motor homunculus. It is frequently classified as part of Broca's area, which is most closely associated with language generation (50-52) and the brain's language networks (53). However, this region is not exclusively recruited by language tasks.…”
Section: Discussionmentioning
confidence: 99%
“…2. Critically, the ROIs have been ordered first by RSN membership (Hacker et al 2013) (see Fig. 7) and, within RSN, by temporal order using latency projections by RSN block.…”
Section: Restingmentioning
confidence: 99%